Innovation and Marketing Strategy for It Services in XYZ Consulting Business at PT XYZ - Yones Fitra Deliyandra; Tongam Sirait (Riviera Publishing, 2024)
PT XYZ, a leading Information Technology (IT) company in Indonesia, has an IT consulting division, XYZ Consulting Services, which is essential in providing IT solutions to clients. Along with the rapid development of Industry 4.0, competition in the IT consulting services sector is getting tougher. Service innovation is key to maintaining a competitive advantage and increasing market share. This research aims to deeply analyze the innovation and marketing strategies implemented by XYZ Consulting Services to strengthen the company's position in the IT consulting market. This research combines interview and observation methods to collect primary and secondary data using a qualitative approach. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and BCG (Boston Consulting Group) matrix were used to identify internal and external factors affecting the company. The research results are expected to determine the types of relevant service innovations and effective marketing strategies that XYZ Consulting Services will implement. In addition, this research will also provide strategic recommendations that can support PT XYZ in achieving its business objectives, namely strengthening its competitive position in the dynamic IT consulting market.